The effects of social media on the food preferences of Generation Z within the scope of gastronomy tourism - Altun, Özlem; Cizrelio?ullari, Mehmet Necati; Babayiğit, Mehmet Veysi (Edward Elgar Publishing Ltd., 2022)
Generation Z named as the period formed by individuals born in 2000 and later can get to the information much more easily as it witnesses technological development. Z generation having both technological equipment and commitment to the virtual world seems to be a smarter and more open generation towards different cultures. The biggest benefit of technology to the lives of people is social media, the communication network. People have started to prefer gastronomy tourism in order to learn and experience the culture of eating and drinking via getting out of the classical holiday concept. The tourism sector has been also affected by this formation and undergone change. The attitudes of Z generation in terms of food and beverage preferences towards gastronomy tourism are evaluated. The importance of the study and its contribution to the literature are pinpointed. The method used in the research is specified. The conclusion and discussion sections are mentioned. © Dogan Gursoy and Rahul Pratap Singh Kaurav 2022.